Monte Carlo dose in a prosthesis phantom based on exact geometry vs streak artefact contaminated CT data as benchmarked against Gafchromic film measurements. (October 2018) - Ade, Nicholas; Oderinde, O.M.; du Plessis, F.C.P.
Highlights: Effect of CT metal artefacts on MC dose in a pelvic prosthesis phantom is studied. 15 MeV electron and 10 MV photon therapy beams were used. An artefact-free phantom model with exactly known materials was reconstructed. For unilateral hip Ti implant, metal artefacts could cause dose errors of about 3%. Abstract: Purpose: In radiotherapy, accurate calculation of patient radiation dose is very important for good clinical outcome. In the presence of metallic implants, the dose calculation accuracy could be compromised by metal artefacts generated in computed tomography (CT) images of patients. This study investigates the influence of metal-induced CT artefacts on MC dose calculations in a pelvic prosthesis phantom. Methods: A pelvic phantom containing unilateral Ti prosthesis was CT-scanned and accurate Hounsfield unit (HU) values were assigned to known materials of the phantom as opposed to HU values produced through the artefact CT images of the phantom. Using the DOSXYZnrc MC code, dose calculations were computed in the phantom model constructed from the original CT images containing the artefacts and artefact-free images made from the exact geometry of the phantom with known materials. The dose calculations were benchmarked against Gafchromic EBT3 film measurements using 15 MeV electron and 10 MV photon beams. Results: The average deviations between film and MC dose data decreased from 3 ± 2% to 1 ± 1% and from about 6 ± 2% to 3 ± 1% for the artefact and artefact-free phantom models against film data for the electron and photon fields, respectively. Conclusions: For the Ti prosthesis phantom, the presence of metal-induced CT artefacts could cause dose inaccuracies of about 3%. Construction of an artefact-free phantom model made from the exact geometry of the phantom with known materials to overcome the effect of artefacts is advantageous compared to using CT data directly of which the exact tissue composition is not well-known.